Management of iatrogenic root perforation with pulp canal obliteration - Aishvarya Kaushik; Sangeeta Talwar; Seema Yadav; Sarika Chaudhary; Ruchika Roongta Nawal (Wolters Kluwer Medknow Publications, 2014)
Iatrogenic root perforations, which may have serious implications, occur in approximately 2-12% of endodontically treated teeth. Successful management of root perforations is dependent on early diagnosis of the defect, location of the perforation, choice of treatment, materials used, host response, and the experience of the practitioner. This report presents the successful management of an iatrogenic perforation in a tooth with radiographic evidence of pulp canal obliteration.